Perianal alveolar rhabdomyosarcoma with pulmonary lymphangitic sarcomatosis: Report of an autopsy case - Koichi Matsumoto; Ryou Ishikawa; Noriko Fuke; Takayuki Yokota; Takayuki Wakabayashi; Yoichi Chiba; Machi Kawauchi; Hitoshi Okada; Takako Yoshioka; Masaki Ueno (Elsevier, 2021)
Background: Childhood rhabdomyosarcoma (RMS) of perineal or perianal origin (PRMS) is rare, accounting for only 2% of all RMSs. PRMS has been reported to show different characteristics depending on the patient's age, and patients aged 10 years or older have a poor prognosis. Disseminated intravascular coagulation (DIC) is considered to be an uncommon complication of RMS. However, it could occur occasionally in patients with widespread RMS with bone marrow infiltration. Pulmonary lymphangitic sarcomatosis (PLS) has been reported to be rare, and to our knowledge, only 18 cases (including 4 patients with RMS) have been reported to date. Case report: A 15-year-old female patient with suspected RMS was admitted to our hospital. The patient was diagnosed with PRMS following radiological evaluations and effusion cytology, and chemotherapy was initiated on the 6th day of admission. During the course, the patient suffered from severe dyspnea and DIC. Despite treatment, the bleeding tendency did not improve, and hepatic and renal failure progressed. The patient died of progressive respiratory failure on the 13th day of admission. An autopsy, performed 2 h after death, revealed a perianal tumor with pseudoalveolar growth pattern. In the lungs, a relatively large number of small metastatic foci, presumed to be lymphatic spread, were identified. It was diagnosed as PLS due to alveolar RMS. Conclusion: Although PLS is reported to be an unexpected form of metastasis, it might cause severe dyspnea in patients with RMS, as 4 of 18 reported cases of PLS are associated with RMS.